Timeless time. Becoming postpresnt (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
Thinking post-present is a contemporary challenge for philosophy. Altered times of technology dissolve the past and the future, becoming post-present. Specially expressed in Digital Eros.
Keywords: Postpresent; Transformation; transit; Desire